The design of plate-girders with appendices on columns and struts, economic columns, and web stresses in plate girders - Lilly, W. E. (Chapman & Hall, 1908)
The analysis of the stresses in the web of the plate-girder is a complex problem. Here, the author's theory of the distribution of stress in the plate-girder is explained.